Development of E-Learning with an Educational Platform Based on Problem-Based Learning to Train High School Students' Understanding of Concepts - Pratiwi, Juli; Sundari, Ayu; Husna, Nadiatul; Ananda, Talia; Rahmad, M (Universitas Lambung Mangkurat, 2024)
E-learning is a system carried out via electronic media, such as computers, tablets, or smartphones. E-learning platforms provide greater flexibility and accessibility for students to access learning materials anytime and anywhere. Based on the analysis conducted, 85.9% of students felt happy with e-learning, and 88.5% of students felt comfortable with e-learning-based learning because the features contained in e-learning helped students understand the material and were easy to use. This research expects to develop and test the validity and practicality of the PBL-based Edukati platform in increasing students' valid and practical understanding of concepts. This research is development research carried out using the ADDIE-type instructional design model. This research was completed only up to the development stage, namely at the validity and practicality stage. In view of the aftereffects of the validity test, the result was 3.30. Based on the results of the teacher's practicality test, the result was 3.88 and the students’ practicality was 3.43, so it tends to be expressed that e-learning with an issue-based learning instructive stage to prepare comprehension understudies might interpret ideas in impulse and momentum material is in the valid and very practical category. Based on the results of the validity and practicality that have been carried out, e-learning with an educational platform based on problem-based learning to train understanding of concepts is suitable for use.